REFLEXIONES SOBRE EL AMBIENTE CULTURAL DE CAMILLA HERCULIANA - Muñoz, Maria (Revista Internacional de Culturas y Literaturas, 2020)
Camilla Herculiana era una boticaria en Padova en el siglo XVI. En 1584 publica sus Lettere di philosophia naturale, en las que debate sobre las causas del Diluvio Universal, la naturaleza del ser humano y la formación del arco iris. Esta obra está escrita en forma de cartas con Georges Garnier y el canciller de Transilvania, Márton Berzeviczy, a los que conoció gracias al ambiente cultural e intelectual de Padua, del que también formaban parte sus interlocutores. Abstract Camilla Herculiana was an apothecary in Padova in the 16th century. In 1584 she published her Lettere di philosophia naturale, in which she discussed the causes of the Universal Flood, the nature of the human being, and the formation of the celestial arc. This work is written in the form of letters with Georges Garnier and the Chancellor of Transylvania, Márton Berzeviczy, whom she met in the cultural and intellectual environment of Padua, of which her interlocutors also belong. The objective of this work is to study and highlight the importance of the environment in which Camilla Herculliana was formed and developed her work.